Brazil : Risk-based Supervision of Brazilian Closed Pension Funds - World Bank (Washington, DC, 2013)
This report provides a comprehensive description of the full process for supporting the new supervisory authority for closed pension funds in Brazil, The National Superintendence for Pension Funds, supervisor of the closed pension fund system in Brazil, or PREVIC, in particular through the development of a revised approach to the risk-based supervision of closed pension funds. This report documents the first-funded World Bank project which, in conjunction with PREVIC, the supervisor of the closed pension fund system in Brazil (established in January 2010), has sought to provide guidance to implement a risk based supervision (RBS) appropriate to Brazilian environment, drawing on international experience. The project ran from January 2010 to March 2012. The key outputs of the project were specified as: i) an assessment of the strengths and weaknesses of the current supervisory benchmarking against best practices in RBS around the world; ii) a roadmap for the implementation of RBS under the circumstances prevailing in the industry; iii) proposals for regulations on selected critical elements for the implementation of RBS framework; and iv) training to supervisors and senior executives of closed pension funds about the main challenges of introducing RBS.